Achieving Predictable Success with Minimal Morbidity: Analysis of the Indirect Sinus Lift Technique for Maxillary Dentally Implant Placement - Khan, Shafi Ullah; Babar, Adnan; Khan, Ali Akhtar; Ishaq, Muhammad; Khan, Shahid Iqbal; Khan, Idrees (Pakistan Armed Forces Medical Journal, 2024)
Objective: To analyze the efficacy of indirect sinus lift procedure for maxillary dental implant placement.Study Design: Prospective analytical study.Place and Duration of Study: 28 Military Dental Centre/ Combined Military Hospital Rawalpindi Lahore, from May 2021 toApril 2023.Methodology: The study included 50 consecutive patients of 40 to 65 years of age presenting with missing upper maxillarymolar teeth with maxillary sinus extension in the alveolar ridge and requiring maxillary dental implant placement. Indirectsinus lift and bone augmentation was carried out through the osteotomy site with concurrent dental implant placement in allpatients.Results: Out of 50 patients 49(98%) have successful osseointegration of dental implant at 4 months follow-up without anysinus complications. The mean procedure time was 25.00+5.00 minutes including osteotomy, bone graft and implantplacement.Conclusion: Elevating maxillary sinus floor presents a crucial step in achieving optimal bone volume for dental implantplacement. Performed meticulously, indirect sinus lift technique is minimally invasive alternative to overcome the surgicalcomplications and risks involved with direct open surgical approach.